Pengembangan Batik Jambi Motif Sungai Penuh sebagai Bentuk Kontribusi Pada Pembangunan - Adhanita, Septiara (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
The existence of small scale and home industries also play a role in regional economic development, as it could become an alternative income for the rural population that undergoes limited agricultural land. At this moment the batik industry was considered as the domain which has the competitive value. Since this type of industry is based on culture which provides the ability to create jobs and increase the income level of the region. However, in the case of batik Jambi with Sungai Penuh’s pattern, the development is relatively stagnant even if this product brings the local characteristic of the region (The script of Incung). By using the Fishbone Diagram and Force Field Analysis (FFA) to determine the main problem of batik Jambi with Sungai Penuh’s pattern, it is found that the issues involved in the development of batik Jambi with Sungai Penuh’s pattern appears in both side: government and craftsmen. So that batik Jambi with Sungai Penuh’s pattern can develop properly, it is necessary that both actors perfect their objective and improve their program in order to create batik Jambi with Sungai Penuh’s pattern as a typical product in the region.